Taxonomy of Dolerus subfasciatus auct. and D. subfasciatus F. Smith with notes on the sawfly subgenus Equidolerus (Hymenoptera, Tenthredinidae) - Heidemaa, Mikk; Smith, David R.; Shinohara, Akihiko (Zootaxa, 2012)
Dolerus (Equidolerus) subfasciatus F. Smith 1874 is a valid species. Dolerus subfasciatus auct. is shown to include threedistinct species: the Nearctic D. (Equidolerus.) neoaprilis MacGillivray, 1908, spec. rev. and two Palaearctic species,D. (E.) pseudoanticus Malaise, 1931, spec. rev. and D. (E.) rhodogaster Zhelochovtsev, 1935, stat. nov. Distributionrecords and imaginal diagnostic characters of the species are provided, and the male of D. (E.) subfasciatus is described.Lectotypes are designated for Dolerus picinus Marlatt, 1898, D. picinus rhodogaster Zhelochovtsev, 1935,D. pseudoanticus Malaise, 1931, and D. yokohamensis Rohwer, 1925. Dolerus lucidus Freymuth, 1870 and D. purusJakowlew, 1891 are associated with the subgenus Equidolerus and D. glabratus Wei, 2002 is transferred from Equidolerus to Dolerus s. str.Kew words: Sawflies, lectotype, nomenclature